Exploring student participation across different arenas of school life. (28th September 2018) - Graham, Anne; Truscott, Julia; Simmons, Catharine; Anderson, Donnah; Thomas, Nigel
Abstract : Much has now been written on student participation at school. Yet a lack of conceptual clarity, contestation over purpose and benefits, and uncertainty about how to culturally embed and effectively facilitate participation in school contexts continue to pose considerable challenges. This article reports the qualitative findings from a large‐scale, mixed‐method study that sought to explore how participation is perceived and practised in schools. The qualitative phase involved students from Years 7–10 ( n = 177) and staff ( n = 32) across 10 government and Catholic secondary schools in New South Wales (NSW), Australia. The data demonstrate that considerable efforts are being made in NSW schools to expand opportunities through which students might 'participate', with these explored across three key arenas of school life: the classroom; co‐curricular activities, including formal participatory structures; and informal relational spaces. Although participatory opportunities were largely ad hoc and often dependent upon the approach of individual teachers or school initiatives, differing enactments of childhood and adulthood were identifiable between the three arenas, along with varying expectations in this regard. The classroom emerged as a positive arena at present, and one in which adult–child relations are beginning to become reconfigured. The co‐curricular arena was much more contested, with the breadth of potential participatory opportunities perhaps distracting from the need to address underlying intergenerational issues. However, informal relational encounters between students and teachers were becoming increasingly egalitarian, and these offer scope for creating the cultural preconditions such that student participation might expand more evenly across school life.